Cowhide Tanning using Caelsalpinia spinosa combined with Oxazolidine - Puente Guijarro, César Arturo (2019)
Mineral tanning (chromium III) is the most used tanning method worldwide, causing harmful environmental effects not only during production, but also after the goods have completed their lifespan and are discarded into landfills. There, contact with oxidizing agents may result in the degradation of trivalent chromium into hexavalent chromium, a highly contaminating compound. This study attempts to determine the effect of tanning using Caelsalpinia spinosa (tara) combined with oxazolidine, to create an environmentally friendly tanning method by replacing chromium III. In conclusion, it is determined that the use of Caelsalpinia Spinosa combined with oxazolidine produces tanned hides with high physical strength properties that exceed technical regulatory quality standards, as well as a sensory appreciation that is attractive for the user of both tanned hides and leather goods.